Effects of triangular and ramp injection rate-shapes on the performance and emissions of a kerosene-diesel fueled direct injection compression ignition engine: A numerical study. (5th January 2017) - Tay, Kun Lin; Yang, Wenming; Zhao, Feiyang; Yu, Wenbin; Mohan, Balaji
Highlights: The start of combustion can be changed by using different injection rate-shapes. Injection rate-shaping causes combustion phasing. The duration of combustion can be controlled through injection rate-shaping. Liquid and vapor penetrations can be controlled by varying injection rate-shapes. Abstract: Diesel engine technology has advanced significantly over the years, giving rise to engines with higher efficiencies and lower emissions. Different injection strategies like multiple injections are employed in order to improve performance and lower emissions. In this work, the effects of triangular and ramp rate-shapes on the combustion process and emissions formation of a direct injection diesel engine are numerically investigated. Two different fuels, which are kerosene and diesel, are used in this work. A reliable kerosene-diesel reaction mechanism is employed with the KIVA4-CHEMKIN code for the numerical simulations. It is found that injection rate-shaping has the capability of changing the start of combustion without changing the start and duration of injection. Moreover, injection rate-shaping controls combustion phasing as well as the duration of combustion. Furthermore, both injection rate-shaping and fuel thermo-physical properties are found to affect the combustion process as well as emissions formation significantly.